Micropropagation of Malaxis acuminata D. Don: A Rare Orchid of High Therapeutic Value - Kaur, Saranjeet; Bhutani, K.K. (Open Access Journal of Medicinal and Aromatic Plants, 2011)
Regeneration potential of pseudobulb segments of Malaxis acuminata, procured from in vitro grown cultures, was analysed in Mitra et al., 1976 medium and its combinations with growth adjuncts. Juvenility of the tissues and chemical stimulus emerged as important factors in eliciting response in the explants. The explants from relatively older pseudobulbs (greater than 0.5cm in length) remained recalcitrant to regeneration whereas those representing younger ones (less than 0.5cm in length) responded positively. The response frequency, pathway of regeneration, and time taken for their development into complete plantlets was directly related to the growth stimulus in the nutrient regime. Shoot buds were induced in an individual treatment with growth regulators (BAP/NAA; 1mg L-1 each) whereas their combination [BAP (1.0 mg L-1) + NAA (1.0 mg L-1)] promoted protocorm-like body formation in the explants. Additional activated charcoal invariably proved beneficial in accelerating the morphogenetic processes leading to plantlet development. NAA (1 mg L-1) impaired the response frequency and delayed subsequent morphogenetic processes leading to plantlet development. BAP+NAA (1.0 mg L-leach)+AC (2 g L-1) was used best for early initiation, highest regeneration frequency, proliferation of protocorm-like bodies (PLB), and plantlet development. Plantlets were transferred to clay pots containing potting mixture (sand, soil, leaf compost) in the ratio of 1:1:1. Nearly 70-80% of plantlets survival was recorded. Histological investigation confirmed that neoformations were dermal and multicellular in origin.